THE EFFECT OF FOOT EXERCISE WITH DIABALL ON INCREASING FOOT SENSITIVITY IN PATIENTS DIABETES MELLITUS AT NUSA INDAH PUBLIC HEALTH CENTER BENGKULU IN 2023 - Neice Shieva Shazhabilla; Septiyanti Septiyanti; Sariman Pardosi; Rahma Annisa; Sahran Sahran (Poltekkes Kemenkes Bengkulu, 2023)
Diabetes Mellitus (DM) is a chronic metabolic disorder resulting from insufficiency of insulin function with many etiologies characterized by high blood sugar levels accompanied by disturbances in carbohydrate, lipid and protein metabolism. The most common complication of DM is peripheral neuropathy which is characterized by decreased sensitivity of foot. The recommended activity to increase foot sensitivity is diabetic foot exercise. In this study, researchers developed a new foot exercise media, namely Diaball. The purpose of this study was to determine whether there was an effect of foot exercise with Diaball on increasing the sensitivity of the foot of DM sufferers at the Nusa Indah Health Center in Bengkulu City. This type of research is a quasi-experiment. With a total sample of 38 people, they were divided into two groups, namely the intervention group of 19 people and the control group of 19 people. The sampling technique in this study was taken using consecutive sampling. The media used were Diaball and a monofilament test instrument. The statistical test using the Mann-Whitney showed a p value of 0.025 (p value ? ? 0.05) so that this could mean that there was an average difference in the sensitivity of the foot before and after the treatment in the intervention group and the control group. So that it can be concluded that there is an effect of foot exercise with Diaball on increasing foot sensitivity in DM sufferers.